2016
DOI: 10.1080/17843286.2016.1237696
|View full text |Cite
|
Sign up to set email alerts
|

Is systematic screening and treatment for latent tuberculosis infection in HIV patients useful in a low endemic setting?

Abstract: A significant decline of TB incidence in HIV patients was observed. Incident TB occurred mainly in African patients, with low CD4 upon HIV diagnosis. A significant proportion of TB cases were discovered early in follow-up which probably reflects TB already present upon HIV diagnosis. In a low endemic setting, exclusion of active TB upon HIV diagnosis remains a priority and screening for LTBI should focus on HIV patients from high risk groups such as migrants from endemic regions, especially in patients with lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In our study, there was a drop of TB incidence (in HIV care) by three-folds following HAART initiation. Patients with higher CD4 and/or CD4/CD8 ratio were at lower risk of TB disease development, as observed in our and previous studies 24,27,28 , as a result of immune recovery 18,19 . The results were consistent with those reported in a study showing the four times higher TB incidence among heterosexual HIV patients not on HAART 29 , and conclusion from a systematic review 19 .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, there was a drop of TB incidence (in HIV care) by three-folds following HAART initiation. Patients with higher CD4 and/or CD4/CD8 ratio were at lower risk of TB disease development, as observed in our and previous studies 24,27,28 , as a result of immune recovery 18,19 . The results were consistent with those reported in a study showing the four times higher TB incidence among heterosexual HIV patients not on HAART 29 , and conclusion from a systematic review 19 .…”
Section: Discussionsupporting
confidence: 89%
“…Year of diagnosis Greater risk among those who entered the cohort later: 1 study 27 Greater risk of TB if diagnosing with HIV during the ART era than prior to ART being introduced: 1 study 41 No association: 3 studies 31,51,54 CD4 count Greater risk at lower CD4 count: 22 studies 23,24,27,28,[30][31][32][33][34][35][36][37][38]40,[42][43][44]46,[49][50][51][52] No association: 3 studies 25,26,39 Viral load Greater risk with higher viral load: 9 studies 23,24,27,31,32,35,36,43,44 No association: 6 studies 25,34,37,49,51,54 Anti-retroviral therapy Lower risk for patients on ART: 10 studies 23,24,…”
Section: Risk Factor For Ltbi Summary Of Resultsmentioning
confidence: 99%
“…We found that the risk of both LTBI and active TB was greatest among PLHIV from ethnic minorities; particularly those of black African, South Asian or Hispanic ethnicity. 13,15,17,19,23,25,31,32,37,43,44,46,49,52,53 Similarly, PLHIV who were born in, or long-term residents of, countries with high TB incidence had higher rates of LTBI and active TB. [10][11][12][13]17,18,[22][23][24]26,45,56 Few studies examined the effects of country of birth and ethnicity independently of each other; those that did found no independent associations between ethnicity and country of birth and active TB 34,46 or LTBI.…”
Section: Ethnicity and Country Of Birthmentioning
confidence: 99%
See 1 more Smart Citation
“…More radically, Dr Maniewsky suggested screening only patients from TB-endemic countries with a nadir (lowest-ever) CD4+ T-cell count <200 cells/mm 3 . This strategy is based on a retrospective study of 1140 HIV-infected patients entering the Brussels St Pierre cohort between 2005 and 2012, and showing that of the 42 patients that would develop TB during follow-up, 83% were of African origin and 60% had a nadir CD4 T-cell count <200 cells/mm 3 [13].…”
Section: Introductionmentioning
confidence: 99%